PERLINDUNGAN HUKUM TERHADAP VARIETAS TANAMAN SERTANI MILIK PEMULIA PETANI DARI KABUPATEN LAMPUNG TENGAH: Legal Protection Of Sertani Plant Varieties Belonging To Farmer Breeders From Central Lampung Regency - Rheyna Hanny Laurencya; Rakhmita Desmayanti (Faculty of Law, Universitas Trisakti, 2024)
The regulation of plant variety protection in Indonesia is regulated in Law No. 29 of 2000 on Plant Variety Protection. Its existence explicitly regulates the appreciation and protection of breeders' rights by minimizing violations and unilateral claims from other parties to a new variety owned by breeders, especially farmers. The article examines whether plant varieties bred by farmers are eligible for rights application and the legal protection mechanism under the PVP Law. This normative research focuses on descriptive literature, using secondary data with primary data support, and applies a qualitative approach with deductive inference. The study concludes that a variety meeting the BUSS requirements and given a name can be registered for protection rights. Ownership of these rights allows the holder to prohibit or permit others from using the variety, ensuring control over its use and distribution. The Sertani plant variety meets all BUSS elements, making it eligible for PVP rights application at the PVTPP Center. These rights provide temporary protection until the issuance of a PVP certificate, ensuring comprehensive legal protection for the variety and supporting farmers in safeguarding their bred plant varieties. This mechanism promotes innovation and fair use within the agricultural sector.